Development and validation of a module for nanoscience and nanotechnology education: a case of pre-service chemistry teachers - Yildirim, Tamer; Kahraman, Sakip (International journal of science education, 2025)
The study aimed to develop and validate a nanoscience and nanotechnology (NST) teaching module for pre-service science teachers in Turkey where NST education has not been formally integrated into the teacher education curriculum. The research, driven by the concurrent triangulation method, was completed in six stages: (1) The content was defined and the syllabus was developed (2) A pilot study was conducted on seven subjects both to evaluate the course plans and activities and to develop the items of the Nanoscience and Nanotechnology Achievement Test (NST-AT) (3) Experts reviewed the items of both the NST-AT and the Nanotechnology Attitude Scale for K-12 teachers (NAS-T) (4) The second pilot study was conducted both to validate the NST-AT and NAS-T and to re-evaluate the course plans and activities (5) Qualitative data collection tools were developed and validated (6) An intervention was performed on 16 subjects to assess whether the NST teaching module presented using an inquiry-based approach was effective on their nanoscience and nanotechnology achievements and attitudes towards nanotechnology. The results showed the NST teaching module had a positive impact on subjects' both cognitive and affective outcomes. The pre-service teachers' views of the activities in the NST teaching module were quite positive.